Carbon production from seasonal litterfall in the Brazilian Atlantic Forest. Issue 2 (3rd April 2021) - Maas, Greyce CB; Sanquetta, Carlos R; Marques, Renato; Machado, Sebastião do A; Sanquetta, Mateus NI; Corte, Ana Paula D; Barberena, Iara M
Abstract : Forests play an important role in climate change, acting as a source or sink of carbon. There is, however, a lack of data regarding the carbon production from litterfall in tropical forests. The Atlantic Forest is one of the most distinguished forest types in Brazil, encompassing the Araucaria Forest. In this study, we assessed the seasonal carbon production from litterfall. Data were collected every season from 27 litter traps. Dry matter and carbon fraction were investigated and confronted with meteorological variables. Litterfall components were stratified into Brazilian pine leaves and twigs: broadleaved leaves, twigs, bark, reproductive material, and other material (miscellaneous). The Tukey test indicated significant differences among the carbon fractions for litter components. Seven key species were determinant in litterfall production. Brazilian pine leaves and twigs were the primary carbon source to the forest, followed by leaves and twigs from broadleaved species. Most carbon input from litterfall comes during spring and summer. We concluded that litterfall is a source of carbon and nutrient to the ecosystem. This study contributes to improving the Brazilian national greenhouse inventory and related reports addressed to climate change mitigation.